The collective to the test of Madness - MAINO, Claudio (Utopía y Praxis Latinoamericana, 2024)
Madness and collective are two terms that have marched in a disjunct way in history. Its most obvious expression was the construction of the psychiatric asylum, located far from the life of the city. The most current incarnation is that of the individual who lives in the street, within the city, but outside of all ties. These individual lives a new exile without asylum in the collective. From my work as a psychologist in a social center in Paris, I ask myself how to integrate the difference of madness, without erasing it in the name of an ideal, inherent to this - and all - collective. I show that collective and madness are structurally disjunct, but for an institution to be alive, the two terms must be inseparable. The collective must be sufficiently docile, so that everyone can appropriate it as a means of life. If the collective is necessary for every speaking being, it is indispensable for those who cannot find a typical solution to the problems posed by their body and the problems it poses to the social body.